MON-512 A De Novo Frameshift Mutation of FAM111B Gene Resulting in Progressive Osseous Heteroplasia in an African American Boy: First Case Report - Panjawatanan, Panadeekarn (J Endocr Soc, 2019)
Introduction: Progressive osseous heteroplasia (POH) is a rare bone disorder characterized by heterotopic ossification in the skin and muscles, resulting in contractures of the joints and progressive loss of function. Whereas 60-70% of the POH patients have paternally inherited inactivating mutations in GNAS gene, the remaining 30-40% harbor no specific etiologies. FAM111B gene mutations, located on chromosome 11q12.1, cause POIKTMP (hereditary fibrosing poikiloderma with tendon contractures, myopathy, and pulmonary fibrosis), a rare autosomal dominant disorder with high frequency of de novo missense mutations, which are believed to cause extensive fibrosis and adiposis of many tissues, though the exact mechanism is unknown. To our knowledge there are no reports of FAM111B associated with POH. Case: We describe a 15-year-old African American boy who presented with generalized calcific nodules, contractures, and muscle weakness leading to immobility, beginning at the age of 6 years. Cutaneous exam showed generalized hard nodules varying from small to plaque-like ulcerated erupted skin lesions. Biochemical evaluation revealed 25(OH) vitamin D insufficiency (20 ng/mL), and normal levels of parathyroid hormone, FGF-23, alkaline phosphatase, calcium, and phosphorus. Skeletal survey radiographs showed extensive heterotopic ossification involving soft tissues and muscles surrounding the bilateral humeri, ulnae, femurs, and bilateral tibias/fibulas. Computed tomography of the chest, abdomen, and pelvis showed extensive muscle ossifications involving right latissimus dorsi, left scalene, bilateral pectoralis and external oblique abdominal, right iliacus, bilateral gluteal, left adductor, and left hamstring. There was also an involvement of the subcutaneous tissues of the right upper back and left lower quadrant of the abdomen, left posterior sacral region, bilateral hips, and the fascia superficial to the erector spinae muscles with no abnormal ossifications in the bones. The clinical and radiographic findings were consistent with POH. Whole Exome Sequencing revealed a de novo heterozygous frameshift mutation in FAM111B (OMIM # 615584) of c.1462delT (p.Cys488Valfs*21) variant, causing replacement of C-terminal region with 21 alternative amino acids. Multiple previously reported disease-associated variants appear to localize within the same domain, supporting the functional importance of this region, though none have been previously associated with POH. Thus, we consider this variant to be pathogenic. Conclusion: This is the first case of POH caused by a mutation in FAM111B gene. Whether POH phenotype could be explained by mutations in FAM111B gene traditionally reserved for POIKTMP remains unclear. Further evaluations are necessary to fully elucidate this finding and potential mechanism by which the FAM111B gene mutation contributes to POH.